The effect of occupational exposure to lead on the non-enzymatic antioxidant system - Michał Dobrakowski; Jolanta Zalejska-Fiolka; Tomasz Wielkoszyński; Elżbieta Świętochowska; Sławomir Kasperczyk (Nofer Institute of Occupational Medicine, 2014)
Background: The role of non-enzymatic antioxidants, such as uric acid, albumin, bilirubin, and α-tocopherol, in lead poisoning remains unclear. Therefore, the aim of the study was to explore the association between occupational exposure to lead and nonenzymatic antioxidant concentrations in serum and plasma. Material and Methods: The study population consisted of 278 healthy male employees of lead-zinc plants, with 129 workers classified as having low lead exposure (blood lead level - PbB = 20-39.9 μg/dl) and 149 workers classified as having high lead exposure (PbB = 40-59.8 μg/dl). The control group was composed of 73 healthy male administrative workers. No one from this group had blood lead level or zinc protoporphyrin (ZPP) level greater than normal levels, being 10 μg/dl and 2.5 μg/g of hemoglobin, respectively. In addition to the levels of PbB and ZPP, serum levels of uric acid (UA), albumin, thiol groups of albumin, and bilirubin were determined. The ferric reducing ability of plasma (FRAP) and the plasma level of α-tocopherol were also evaluated. Results: Lead exposure indices were significantly elevated in the examined subgroups as compared with the controls. Serum uric acid levels were significantly elevated in both subgroups, particularly in the group with high exposure. Serum bilirubin concentration was significantly elevated in the group with high exposure compared with the control group, while in the group with low exposure, it showed only a non-significant trend towards an increase. In contrast, ferric-reducing ability of plasma was not significantly greater in the examined subgroups as compared with the control group. Nevertheless, levels of albumin, thiol groups of albumin, and α-tocopherol levels were significantly decreased in the exposed subgroups compared with the control group. Conclusions: Occupational exposure to lead interferes with the blood non-enzymatic antioxidant system. Med Pr 2014;65(4):443-451